Volumetric capnography versus spirometry for the evaluation of pulmonary function in cystic fibrosis and allergic asthma - Armando Almeida‐Junior; Fernando Augusto Lima Marson; Celize Cruz Bresciani Almeida; Maria Ângela Gonçalves Oliveira Ribeiro; Ilma Aparecida Paschoal; Marcos Mello Moreira; José Dirceu Ribeiro (Brazilian Society of Pediatrics, 2020)
Objective: To compare the values of the markers for volumetric capnography and spirometry and their ability to classify children and adolescents with asthma, cystic fibrosis (CF), and healthy controls. Methods: This was a cross‐sectional study that included 103 patients with controlled persistent allergic asthma, 53 with CF and a healthy control group with 40 volunteers (aged 6-15 years), of both sexes. The individuals underwent volumetric capnography and spirometry. Results: Phase III slope (SIII), SIII standardized by exhaled tidal volume (SIII/TV) and capnographic index (SIII/SII) × 100 (KPIv) were different among the three groups assessed, with highest values for CF. The relation between the forced expiratory volume in one second and the forced vital capacity (FEV1/FVC) was the only spirometric marker that presented difference on the three groups. On individuals with normal spirometry, KPIv and FEV1/FVC were different among the three groups. The ROC curve identified the individuals with asthma or CF from the control group, both through volumetric capnography (better to identify CF in relation to the control using KPIv) and through spirometry (better to identify asthma in relation to the control). KPIv was the best parameter to distinguish asthma from CF, even in individuals with normal spirometry. Conclusion: Volumetric capnography and spirometry identified different alterations in lung function on asthma, CF, and healthy controls, allowing the three groups to be distinguished. Resumo: Objetivo: Comparar os valores dos marcadores para capnografia volumétrica e espirometria e sua capacidade de classificar crianças e adolescentes com asma, fibrose cística (FC) e controles saudáveis. Métodos: Foi realizado um estudo transversal que incluiu 103 pacientes com asma alérgica persistente controlada, 53 com FC e um grupo controle saudável com 40 voluntários (6 a 15 anos), de ambos os sexos. Os indivíduos foram submetidos a capnografia volumétrica e espirometria. Resultados: O slope da fase III (SIII), SIII padronizada pelo volume tidal exalado (SIII/VT) e o índice capnográfico (SIII/SII) × 100 (KPIv) foram diferentes entre os três grupos avaliados, com maiores valores para o grupo FC. A relação entre o volume expiratório forçado no primeiro segundo e a capacidade vital forçada (VEF1/CVF) foi o único marcador de espirometria com diferenças nos três grupos. Nos indivíduos com espirometria normal, o KPIv e VEF1/CVF foram diferentes entre os três grupos. A curva ROC diferenciou os indivíduos com asma ou FC daqueles do grupo controle, ambos através da capnografia volumétrica (melhor para identificar a FC em relação aos controles pelo KPIv) e por meio da espirometria (melhor para identificar a asma em relação aos controles). O KPIv foi o melhor parâmetro para distinguir a asma da FC, mesmo em indivíduos com espirometria normal. Conclusão: A capnografia volumétrica e a espirometria identificaram diferentes alterações de função pulmonar na asma, na FC e nos controles saudáveis, permitiram que os três grupos fossem diferenciados. Keywords: Asthma, Cystic fibrosis, Pulmonary function, Spirometry, Volumetric capnography, Palavras‐chave: Asma, Fibrose cística, Função pulmonar, Espirometria, Capnografia volumétrica